Representasi kecantikan pada musik video Mantra Jennie: studi semiotika Barthesian - Angelia Ulfimudana Piliang; Rino Andreas (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2026)
Abstract This research is driven by the complex and multi-dimensional nature of beauty, which is frequently confirmed to rigid, patriarchal physical standards, particularly within the K-pop industry’s “Korean Beauty Standard.” Media, specifically music videos, serve as pivotal instruments in disseminating these values, yet they also function as arenas for deconstructing stereotypes. Jennie’s Mantra was selected as the study object because it represent a shift in the meaning of beauty, moving from mere visual aesthetics to a form of self-empowerment and inner strength aligned with global feminist movements. The objective of study is analyze the representation of beauty in the Mantra music video through Roland Barthes’ perspective to understand how beauty is constructed within the context of contemporary popular culture. The methodology employed is qualitative, utilizing Roland Barthes’ semiotic approach to dissect signs through three layers of meaning denotation, connotation, and myth. data were collected through in dept observation of the lyrics and visual elements within the music video. The findings reveal that beauty in Mantra is not singular but is constructed into four primary categories. Empowering beauty, emphasizing control and strength, Inclusive beauty, celebrating ethnic diversity, prestige beauty, linking beauty to social status and global success, and beauty as a medium for freedom of expression. In conclusion, the study assert that Jennie successfully shifts the myth of beauty from a passive object judged by society into an autonomous, empowered subject. This representation demonstrates that beauty now function as a means of articulating female identity and agency within a highly competitive entertainment industry Keyword: Beauty representation; semiotics; Roland Barthes, music video, popular culture.   Abstrak Studi ini muncul dari masalah standar kecantikan yang kerap terpaku pada bentuk fisik kaku dan berbau patriarki, terutama pada dunia K-Pop yang begitu melekat dengan Korean Beauty Standard. media seperti video musik punya andil besar dalam menyebarkan nilai-nilai tersebut, tetapi sekaligus dapat menjadi ruang untuk membongkar stereotip-stereotip tersebut. Lagu Mantra milik Jennie menjadi fokus studi karena lagu ini menandai perubahan arti kecantikan dari sekadar tampilan luar menuju pemberdayaan diri dan kekuatan inner yang selaras dengan gelombang feminisme global. Penelitian ini bertujuan untuk mengurai representasi kecantikan di musik video Mantra melalui kacamata Roland Barthes, sehingga bagaimana konsep kecantikan direkonstruksi di tengah budaya populer dapat dipahami. Studi ini menggunakan metode kualitatif dengan semiotika milik Barthes, yang mengupas tanda-tanda lewat tiga tingkatan makna denotasi, konotasi, dan mitos. datanya diambil dari pengamatan teliti terhadap lirik lagu dan visual-visual di video musiknya. Hasil studi ini mengungkapkan bahwa kecantikan dalam Mantra tidak bersifat tunggal, tetapi terbagi menjadi 4 kategori. Empowering beauty menyoroti kendali dan kekuatan pribadi, Inclusive beauty menyoroti keberagaman ras dan etnis, prestige beauty yang menghubungkan cantik dengan status sosial serta kesuksesan global, dan kecantikan sebagai kebebasan dan ekspresi diri. Jennie mengubah mitos kecantikan dari pasif yang dinilai menjadi subjek mandiri yang berkuasa. Hal tersebut menjadi bukti kalau kecantikan sekarang menjadi alat untuk mengungkapkan identitas dan kekuatan perempuan di industri hiburan. Kata-kata Kunci: Representasi kecantikan; semiotika; Roland Barthes; musik video; budaya populer.